(untitled) (Research, Society and Development, 2021)
Standardized germination and tetrazolium test protocols are important for the analysis of seeds of Aspidosperma pyrifolium, a forest species of economic value and still poorly studied according to the literature, which is the objective of the present work. Thus, the following were tested: Germination (effect of substrates and temperatures) and Tetrazolium (effects of soaking and immersion times in concentrations of the tetrazolium solution). For the germination test, the paper roll and vermiculite substrates and temperatures of 25, 30 and 25-30ºC showed the best values (means between 65-90% germination). In the tetrazolium test, the treatment with 10 hours of soaking and 3 hours of immersion in the solution with a concentration of 0.075% (average of 90% viability) was the best. A positive correlation (Pearson) was found between the use of paper substrate at 25ºC and the abovementioned Tetrazolium treatment. Both described protocols [Germination (paper substrate at 25ºC for eight days) and Tetrazolium (10h of imbibition and 3h of immersion in the solution with a concentration of 0.075%)] can be tested in seeds of other populations of this species for their effectiveness.